Sex Differences in Intracranial Atherosclerotic Plaques Among Patients With Ischemic Stroke - Yan, Xuejiao; Tang, Min; Gao, Jie; Wang, Lihui; Li, Ling; Ma, Niane; Shi, Xiaorui; Lei, Xiaoyan; Zhang, Xiaoling (Frontiers in Cardiovascular Medicine, 2022)
Objective High-risk intracranial arterial plaques are the most common cause of ischemic stroke and their characteristics vary between male and female patients. However, sex differences in intracranial plaques among symptomatic patients have rarely been discussed. This study aimed to evaluate sex differences in intracranial atherosclerotic plaques among Chinese patients with cerebral ischemia. Methods One hundred and ten patients who experienced ischemic events underwent 3T cardiovascular magnetic resonance vessel wall scanning for the evaluation of intracranial atherosclerotic disease. Each plaque was classified according to its likelihood of causing a stroke (as culprit, uncertain, or non-culprit). The outer wall area (OWA) and lumen area of the lesion and reference sites were measured, and the wall and plaque areas, remodeling ratio, and plaque burden (characterized by a normalized wall index) were further calculated. The composition (T1 hyperintensity, enhancement) and morphology (surface irregularity) of each plaque were analyzed. Sex differences in intracranial plaque characteristics were compared between male and female patient groups. Results Overall, 311 plaques were detected in 110 patients with ischemic stroke (81 and 29 male and female patients, respectively). The OWA (P < 0.001) and wall area (P < 0.001) of intracranial arterial lesions were significantly larger in male patients. Regarding culprit plaques, the plaque burden in male patients was similar to that in female patients (P = 0.178, odds ratio [OR]: 0.168, 95% confidence interval [CI]: −0.020 to 0.107). However, the prevalence of plaque T1 hyperintensity was significantly higher than that in female patients (P = 0.005, OR: 15.362, 95% CI: 2.280–103.49). In the overall ischemic stroke sample, intracranial T1 hyperintensity was associated with male sex (OR: 13.480, 95% CI: 2.444–74.354, P = 0.003), systolic blood pressure (OR: 1.019, 95% CI: 1.002–1.036, P = 0.031), and current smoker (OR: 3.245, 95% CI: 1.097–9.598, P = 0.033). Conclusion For patients with ischemic stroke, the intracranial plaque burden in male patients was similar to that in female patients; however, the plaque characteristics in male patients are associated with higher risk, especially in culprit plaques.